2015
DOI: 10.1159/000441152
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Choroidal Vascular Changes in Patients with Multiple Sclerosis Using Enhanced Depth Imaging Optical Coherence Tomography

Abstract: Objective: To evaluate the choroidal thickness in patients with multiple sclerosis (MS) using enhanced depth imaging optical coherence tomography (EDI-OCT). Methods: In this observational comparative study, 68 eyes of 34 MS patients and 60 eyes of 30 healthy subjects were evaluated. All participants underwent complete ophthalmologic examination and OCT scanning. Choroidal thickness measurements were performed at seven points. Results: The mean subfoveal choroidal thickness was reduced significantly in MS patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 25 publications
(50 reference statements)
4
23
0
2
Order By: Relevance
“…They suggested that RNFL can be used as a marker of white matter damage in MS. Chatziralli et al [3] evaluated RNFL thickness in optic neuritis associated with MS. Similar to Esen et al [1], they found a reduced average-RNFL thickness in MS eyes with optic neuritis. However, they also reported that inferior- and temporal-quadrant RNFL thickness is different between eyes with optic neuritis and control eyes.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…They suggested that RNFL can be used as a marker of white matter damage in MS. Chatziralli et al [3] evaluated RNFL thickness in optic neuritis associated with MS. Similar to Esen et al [1], they found a reduced average-RNFL thickness in MS eyes with optic neuritis. However, they also reported that inferior- and temporal-quadrant RNFL thickness is different between eyes with optic neuritis and control eyes.…”
supporting
confidence: 82%
“…We read the article by Esen et al [1] entitled ‘Evaluation of choroidal vascular changes in patients with multiple sclerosis using enhanced depth imaging optical coherence tomography' with great interest. The authors evaluated the choroidal thickness changes in patients with multiple sclerosis (MS) using optical coherence tomography.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown in the literature that age, sex, diurnal variation, systemic/local diseases and their treatment, intraocular pressure, and many other factors have effect on CT [2,3]. Although Esen et al [1] have specified many factors in their study, we would like to address some points, which may also be important to consider.…”
mentioning
confidence: 98%
“…We have read and reviewed the article by Esen et al [1 ]entitled ‘Evaluation of choroidal vascular changes in patients with multiple sclerosis using enhanced depth imaging optical coherence tomography' with great interest. The authors examined the choroidal thickness (CT) in 68 eyes of 34 multiple sclerosis (MS) patients by using enhanced depth imaging optical coherence tomography.…”
mentioning
confidence: 99%